The International Polar Year 2007-08 and the development of portuguese research on Antarctic permafrost - Vieira, Gonçalo (2009)
portuguese Antarctic permafrost research has developed fast in the last decade. The research was initiated by the centre for Geographical Studies of the university of lisbon in the framework of a collaboration with the university of Alcalá (Spain) and the Spanish Antarctic programme in 1999. In 2007 and 2008, collaborations have extended, respectively to the bulgarian and Argentinean programmes. The critical mass has grown substantially since then and other institutions are now also involved on the research activities. The development of scientific activities was fostered by the International polar year 2007-08 and supported by funding from public and private institutions. A wide-scope education and outreach project has significantly contributed to the public and political awareness of the science programme, and a close interaction between scientists and society has developed. The main research topics are permafrost, active layer and geomorphological processes monitoring, with an emphasis on detection of climate change signals.